PMA Muadalah sebagai Tantangan dan Peluang Meningkatkan Standar Pendidikan Pesantren - Siti Aimah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
Education in pesantren, in general, from time to time is almost unchanged. The concept of “al-Muhaafadhatu ala 'al-qadiimi as-shaalih wa al-jahdu bi al-Jadiidi al-ashlah” implies pesantren through consistently maintaining the spirit of pesantren by providing education oriented to "tafaqquh fi ad-diin", however the transformation of the pesantren education system also conducted by leaders of pesantren to maintain the existence of pesantren so that education is more acceptable to the wider community, among the ways taken is equalizing the level of education with government support with the issuance of the Minister of Religion Regulation (PMA) Muadalah (equalization) number 18 of 2014. This is an opportunity for pesantren in the midst of the modernization of the education system in Indonesia, on the other hand pesantren as the oldest educational institution is still recognized as a native Indonesian educational institution. In addition, it is also a challenge for pesantren to prove that only pesantren which until now have been accepted by the wider community as an educational institution that prioritizes moral education in the midst of the failure of the general education system which makes morals only material